Epidemiological Changes in Hospitalized Bronchiolitis in Children Under 2 Years of Age in Hangzhou Before and After COVID-19 Restriction Easing - Xu X; Chen X; He J; Su L; Tong X; Sun Y; Huang S; Bai G; Chen Z (Infection and Drug Resistance)
Xuchen Xu,1,* Xiya Chen,1,* Jing He,1,* Lin Su,1 Xudong Tong,2 Ying Sun,1 Shumin Huang,1 Guannan Bai,1 Zhimin Chen1 1Department of Pulmonology, Children’s Hospital, Zhejiang University School of Medicine, National Clinical Research Center for Child Health., Hangzhou, Zhejiang, People’s Republic of China; 2Department of Paediatrics, Cixi Maternity and Child Health Care Hospital, Ningbo, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhimin Chen; Guannan Bai, Email zmchen@zju.edu.cn; guannanbai@zju.edu.cnBackground: Bronchiolitis is a common cause of hospitalization in infants under 2 years of age. The epidemiological effects of changes in hygiene and social behaviors during COVID-19 restrictions on the disease is still debated. This study aimed to analyze the changes in the viral etiology of bronchiolitis in Hangzhou during the COVID-19 restriction period (2022) compared to the period following the easing of restrictions(2023).Methods: This study collected data on patients under 2 years of age who were admitted for bronchiolitis to the Department of Pulmonology at the Children’s Hospital, Zhejiang University School of Medicine (Hangzhou) from January, 1, 2022, to December 31, 2023. It also investigated seasonal variations in the incidence of bronchiolitis and pathogen distribution across different years.Results: This study included a total of 697 children with bronchiolitis, with a median age of 7.5 (4.2– 12.0) months. Of these, 68.9% were boys and 31.1% were girls. Compared to 2022, the number of bronchiolitis cases in 2023 (388 versus 309) and their proportion of lower respiratory tract infections (39.1% versus 28.2%) have significantly increased (p < 0.001). Whether in 2022 or 2023, respiratory syncytial virus (RSV) was the primary pathogen causing bronchiolitis among children under 12 months of age, while human rhinovirus (HRV) was the main pathogen in children aged 12– 24 months. There was a shift in the timing of the peak of several viruses including RSV, human metapneumovirus (HMPV) and parainfluenza virus (PIV) infections in 2023. However, the epidemic trend of HRV presented no significant changes between 2022 and 2023.Conclusion: The findings suggest that bronchiolitis hospitalizations increased markedly after COVID-19 restriction easing, particularly among children aged 12– 18 months. There was a shift in the timing of the peak of several viruses including RSV, HMPV and PIV infections in 2023, emphasizing the need for hospitals to anticipate potential irregularities in time in the future.Keywords: RSV, COVID-19, bronchiolitis, non-pharmaceutical interventions